212. RapidArc versus IMRT for postoperative irradiation of a case of recurrent breast cancer with internal mammary lymph node involvement. (December 2018) - Tamborra, P.; Bettiol, M.; Carbonara, R.; Rito, A. Di; Lioce, M.; Milella, A.; Nardone, A.; Necchia, R.; Didonna, V.; Massafra, R.
Abstract : Purpose: The aim of this case-report is a dosimetric comparison between RapidArc and IMRT treatment plans for a recurrent breast cancer with internal mammary chain (IMC) involvement. Methods: A 46 years old woman with peri-prosthetic recurrent breast cancer was evaluated for postoperative left chest wall and homolateral periclavicular and IMC irradiation, with the inclusion of internal mammary lymph node (IMN) that uptaked fluoro-deoxyglucose at postoperative PET. Prescription dose (PD) to PTV (left chest wall and homolateral IMC) was 50 Gy(2 Gy/die); PD to left periclavicular region was 46, 8 Gy (1, 87 Gy/die); the PET-positive IMN received a simultaneous integrated boost up to 59, 25 Gy (2, 37 Gy/die; EQD2 of 64 Gy with estimated α / β 3). A 1 cm-tissue equivalent bolus was used on the skin. We compared RapidArc with 5-beams step-and-shot IMRT plans according to target coverage, conformity and dose-homogeneity index, Organs at Risk (OARs) sparing (heart, lungs, spinal cord). Controlateral breast was not evaluated because of a previously implanted prosthesis. Number of monitor units (MU) and treatment delivery time were also considered. Daily image-guided radiotherapy was performed in order to reduce inter fraction organ motion. Results: RapidArc achieves better PTV and boost dose coverage and dose-homogeneity compared to IMRT. RapidArc also allows a better normal OARs sparing, with fewer monitor units and shorter delivery time. Target coverage and dose-sparing for OARs were not acceptable with 3DCRT because of chest's anatomical conformation. Conclusion: Our dosimetric results confirmed that RapidArc allows to obtain optimal target-coverage and adequate dose-sparing for OARs as reported in literature[1] . It could be appropriate to reduce the respiration-induced intra-fraction target motion using breath-hold techniques.